2018
DOI: 10.1007/s10943-018-0597-z
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Fitness for Military Veterans: A Curriculum Review and Impact Evaluation Using the Duke Religion Index (DUREL)

Abstract: Suicide rates among military veterans exceed those found in the general population. While the exact reasons for these high rates are unknown, contributing factors may include the military's perceived rejection of patient identities, creating barriers to mental health care within the clinical sector and a mandate for prevention programs. Spiritual fitness has emerged over the last decade as an important concept in human performance optimization and is included among holistic approaches to developing and maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…The results of the present study showed that soldiers had high SWB. Other studies in Iran (33)(34)(35) and the USA (36) are in line with the present study. Perhaps, one rea-son for the high SWB score in soldiers is the cultural and social characteristics that dominate the Iranian society.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study showed that soldiers had high SWB. Other studies in Iran (33)(34)(35) and the USA (36) are in line with the present study. Perhaps, one rea-son for the high SWB score in soldiers is the cultural and social characteristics that dominate the Iranian society.…”
Section: Discussionsupporting
confidence: 93%
“…Scores were summed to create total and subscale scores, with higher scores indicating higher degrees of religiosity. The DUREL has demonstrated good test–retest reliability and convergent validity among veteran populations (Koenig & Büssing, 2010; K. H. Thomas et al, 2018). In the present study, Cronbach's alpha for the total and IR scales were .94 and .93, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…27 The results of this study showed that the soldiers' SWB was high. Numerous studies in the USA, 28,29 (, Australia, 30 and Iran 1,31 revealed high levels of SWB in participants. One of the reasons for high SWB score of the Iranian military soldiers can be the cultural and social characteristics ruling this society; in Iran, spirituality is intertwined with the social, cultural, and family dimensions of the individuals.…”
Section: Discussionmentioning
confidence: 99%